The McKenzie Method and its association with psychosocial outcomes in low back pain: a systematic review. (2nd December 2021) - Kuhnow, Alexi; Kuhnow, Jason; Ham, David; Rosedale, Richard
ABSTRACT: Study Design : Systematic Literature Review. Background : The McKenzie Method (MDT) is a comprehensive conservative approach commonly used for the management of low back pain (LBP); however, its association with psychosocial outcomes in this population is less clear. Objectives : Evaluate whether MDT has an association with psychosocial outcomes for individuals with LBP. Methods : The following electronic databases were searched: Medline, Pubmed, Cochrane, CINAHL, Embase and AMED. They were systematically searched from the date of inception to August 2019. Included studies had to have participants experiencing LBP who were over 18 years old, utilize MDT as an assessment or intervention, and report outcomes for at least one psychosocial variable. Three reviewers independently evaluated methodological quality of randomized control trials (RCT) using the PEDro scale and observational studies using the GRACE scale. Results : The initial search resulted in 181 articles to review. After screening abstracts, then full articles, a total of 16 studies were included, 5 of which were RCTs rated 5-8/10 on the PEDro scale. A qualitative review was performed and the studies' results were synthesized into five main findings: fear-avoidance beliefs, depression symptoms, pain self-efficacy, psychological distress, and return to work (RTW). Conclusions : There is evidence that MDT has an association with improving fear-avoidance beliefs, pain self-efficacy, depression, and psychological distress. These results should be interpreted with caution as further high-quality randomized control trials addressing this topic are necessary due to the varying methodological and statistical constructs of the included studies.